Efficient drug delivery of β-estradiol encapsulated in Zn-metal–organic framework nanostructures by microwave-assisted coprecipitation method - Ranjbar M; Pardakhty A; Amanatfard A; Asadipour A (Dove Medical Press, 2018)
Mehdi Ranjbar,1,2 Abbas Pardakhty,1,3 Arezou Amanatfard,1 Ali Asadipour1,3 1Pharmaceutics Research Center, Institute of Neuropharmacology, Kerman University of Medical Sciences, Kerman, Iran; 2Student Research Committee, Kerman University of Medical Sciences, Kerman, Iran; 3Faculty of Pharmacy, Kerman University of Medical Sciences, Kerman, Iran Abstract: Metal–organic frameworks (MOFs) are structures made up of inorganic nodes, which can be either single ions or clusters of ions and organic linkers. This study reports on a novel processing route for producing β-estradiol encapsulated in Zn-MOF nanocomposites by microwave-assisted coprecipitation as a facile and fast method. Zn-MOF nanocomposites were synthesized with the aid of Zn(OAc)2·2H2O and 2,6-pyridine dicarboxylic acid ammonium as an organic ligand. Furthermore, we studied encapsulated β-estradiol which is one of the most important classes of estrogenic compounds that are used in the treatment of prostate cancer and breast cancer. The effects of β-estradiol concentration and microwave irradiation on the morphology, particle size, distribution, and in vitro photoluminescence spectroscopy experiments of β-estradiol entrapped in Zn-MOF nanocomposites were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, ultraviolet–visible spectroscopy, Fourier transform infrared spectroscopy, and Brunauer–Emmett–Teller spectroscopy. These nanostructures can be a good option for thawing hydrophilic and hydrophobic drugs over time. Zn-MOF nanocomposites with high porosity, total pore volume (0.04665 cm3g-1), and nanostructures have provided the platform to load β-estradiol such as low soluble drugs. Maximum of drug release was about 82% at pH 8.9 after 8 h. Keywords: nano structures, drug delivery, encapsulation, drug design, β-estradiol